GATA3 as a master regulator and therapeutic target in ovarian high‐grade serous carcinoma stem cells. Issue 12 (3rd October 2018) - Chen, Hsiang‐Ju; Huang, Rui‐Lan; Liew, Phui‐Ly; Su, Po‐Hsuan; Chen, Lin‐Yu; Weng, Yu‐Chun; Chang, Cheng‐Chang; Wang, Yu‐Chi; Chan, Michael Wing‐Yan; Lai, Hung‐Cheng
Abstract : Ovarian high‐grade serous carcinoma (HGSC) is the most lethal gynecological malignancy. Prevailing evidences suggest that drug resistance and recurrence of ovarian HGSC are caused by the presence of cancer stem cells. Therefore, targeting cancer stems is appealing, however, all attempts to date, have failed. To circumvent this limit, we analyzed differential transcriptomes at early differentiation of ovarian HGSC stem cells and identified the developmental transcription factor GATA3 as highly expressed in stem, compared to progenitor cells. GATA3 expression associates with poor prognosis of ovarian HGSC patients, and was found to recruit the histone H3, lysine 27 (H3K27) demethylase, UTX, activate stemness markers, and promote stem‐like phenotypes in ovarian HGSC cell lines. Targeting UTX by its inhibitor, GSKJ4, impeded GATA3‐driven stemness phenotypes, and enhanced apoptosis of GATA3‐expressing cancer cells. Combinations of gemcitabine or paclitaxel with GSKJ4, resulted in a synergistic cytotoxic effect. Our findings provide evidence for a new role for GATA3 in ovarian HGSC stemness, and demonstrate that GATA3 may serve as a biomarker for precision epigenetic therapy in the future. Abstract : What's new? Cancer stem cells (CSCs) routinely evade conventional cancer therapies and fuel tumor regrowth. However, while CSC targeting is an appealing therapeutic strategy, studies are needed to better understand CSC differentiation. Here, in multipotent CSCs from ovarian high‐grade serous carcinomas (HGSCs), complexes consisting of the stemness regulator GATA3 and the histone demethylase UTX were found to maintain cancer stemness via epigenetic activation of c‐MYC, CD44, and NANOG. GATA3 was further identified as an independent risk factor in early‐stage ovarian HGSC. The results suggest that GATA3 is a prognostic marker in ovarian tumorigenesis and that targeting GATA3/UTX is a promising therapeutic approach.